Nurses’ knowledge and willingness to recommend malaria vaccination to caregivers of under-5 in Nigeria: a nationwide survey - Olumide T. Adeleke; Mary A. Oboh; Oludamola V. Adeleke; Titilope A. Awotunde; Dolapo E. Ajala; Timothy K. Samson; Adepeju O. Adegoke (Malaria Journal)
Abstract Background Malaria is a major public health problem in Nigeria. This study set out to ascertain Nigerian nurses' knowledge and willingness to recommend malaria vaccination to caregivers of under-5 children. Methods This was a cross-sectional study carried out among nurses from all six geopolitical zones of Nigeria. A pretested semi-structured questionnaire was used to collect data on participants' demographics, their knowledge of the RTS S/AS01 and R21 Matrix M malaria vaccines, how they obtain malaria vaccine-related information, and the factors that the nurses consider when recommending any malaria vaccine. Univariate association between each of the demographics characteristics and the key research variables: knowledge of the vaccine and willingness to recommend was used. This was examined using the Chi-Square test and multiple logistic regression. Results The study found that nearly two out of every three nurses had poor knowledge and perception of the vaccines (p < 0.05). Awareness of the malaria vaccine was the only factor that was found to be associated with their knowledge (p <0.05). The odds of willingness to promote the vaccine were about 21 times higher among nurses with high perceptions of efficacy than their counterparts who have low perceptions. Conclusions The findings highlight major gaps in Nigerian nursing's knowledge and awareness of malaria vaccinations, as well as their willingness to recommend the vaccine to parents. Addressing these gaps will enable nurses to play a critical role in the successful implementation of malaria immunization campaigns, lowering the illness burden among vulnerable populations.